2018
DOI: 10.1080/1065657x.2018.1528908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vermicompost Tea on Faba Bean Growth and Yield

Abstract: This study investigatecl the effect of vermicompost tea (VCT) as a natural foliar fertilizer in faba bean. To determine the effect of ver at different doses on the growth and reproduc tion of faba bean, ver was producecl and three different concentrations (0, 10, and 20% VCl) were appliecl as a foliar fertilizer to faba bean plants. Plant height, number of flowers, and pods per plant as well as soluble sugars were measurecl weekl y after treatment for a period of 11 weeks. Treatecl plants were larger and had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…Other studies performed on vermicompost tea or vermicompost leachate reported plant growth benefits and increased tolerance against abiotic stress. For example, Chaichi et al, 2018 [ 59 ] applied different concentrations of vermicompost tea ranging from 0% to 20%, as a foliar amendment in faba bean and they found that treated plants grow better than controls and had more flowers, clumps and pods per plant than non-treated pants [ 59 ]. Treatment at a concentration of 10% of vermicompost tea showed better results that 20%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies performed on vermicompost tea or vermicompost leachate reported plant growth benefits and increased tolerance against abiotic stress. For example, Chaichi et al, 2018 [ 59 ] applied different concentrations of vermicompost tea ranging from 0% to 20%, as a foliar amendment in faba bean and they found that treated plants grow better than controls and had more flowers, clumps and pods per plant than non-treated pants [ 59 ]. Treatment at a concentration of 10% of vermicompost tea showed better results that 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment at a concentration of 10% of vermicompost tea showed better results that 20%. The authors attributed these growth benefits the presence of nutrients, humic acid and putative hormones in vermicompost tea [ 59 ]. Other reports showed vermicompost leachate, a method consisting of adding water to a large amount of vermicompost (e.g., 20 L of water for 50 kg of vermicompost) allowing the mixture to leachate for 48 h, alleviated salt stress in tomato plants which was also explained by phytohormones and presence of other compounds such as humic acid and antioxidants [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Dhary and Al-Baldawi (2017) showed that the application of organic fertilizers significantly increases yield of faba bean seeds. However, Chaichi et al (2018) indicated that vermicomposting tea is a useful fertilizer to improve growth in faba bean.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented the impacts of compost and vermicompost tea in suppressing pests and diseases (Scheuerell and Mahaffee, 2002). This tea can also have positive effects on crop physiology, growth and yield (Benitez et al, 1996;Pant et al, 2009;Gutiérrez-Miceli et al, 2011;Chaichi et al, 2018;Arancon et al, 2019;Ibrahim et al, 2019, and many others). Pant et al (2012) directly linked increased pak choi plant growth with the mineral N and gibberellin content of compost tea.…”
Section: Introductionmentioning
confidence: 99%